SELECTION OF HAZARD IDENTIFICATION AND RISK ASSESSMENT METHOD AND ITS IMPLEMENTATION IN PRODUCTION PROCESS OF COMPANY X BY USING AHP (ANALYTICAL HIERARCHY PROCESS) - Purba (NIM : 25315021), Lamtua
Efforts to reduce and prevent occupational accidents are to identify hazards and risk assessment. However, many manifacturing companies have not implemented these activities, including company x in Bandung. There are several types of methods that can be used for identifying hazards such as JHA, FMEA, and What-if, but each method has advantages, disadvantages, and differences in its implementation procedures. AHP (Analitycal Hierarchy Process) is used for decision making in determining the appropriate hazard identification method to be applied to company x. Expert respondents involved in AHP questionnaires come from internal and external company x, where respondents are those who work in OSH field, have received training or certified, understand hazard identification and risk assessment. The results of decision making by company x based on AHP assessment for all respondent groups by looking at AHP analysis (number of respondents most representing respondents internal and external company x). The result of assessment based on joint respondent (consistency assessment ≥75%) become the basis in determining the alternatives of the selected method, where What-if has the highest weight (0.378), followed by JHA (0.357), and FMEA (0.265). What-if then becomes the preferred method to be applied to company x. The advantages of What-if method are the least costly expenses, the fastest analysis time, the minimum number of team personnel and documentation required, and the team's minimum required skills compared to JHA and FMEA methods. From the hazard identification result using the What-if method, the highest risk score (300) comes from sawing, turning, turn-mill, and milling units caused by the source of gravity hazard.